Cultural Economics and Intellectual Property: Tensions and Challenges for the Region. Issue 2 (3rd March 2015) - Forsyth, Miranda
Abstract: The Pacific islands region is currently experiencing an intensification of interest in culture as an enabler, rather than an inhibitor, of development. The emerging field of cultural economics seeks to chart ways in which culture can lead to both economic development and also to other goals, such as positive social relationships, community cohesion and maintenance and enjoyment of cultural heritage. However, bringing together these different range of goals at times involves tensions, often manifested in differences between individual autonomy and family and community obligations, generational focus and clashes of cultural logics. This paper investigates these tensions through the lens of intellectual property, an area where competing ideologies and perspectives of entitlement often come head to head. It identifies and reflects upon four areas of tension that will have to be navigated as the region experiments with both global models of intellectual property and national and local regulatory mechanisms.